QOLP-29. MINDFULNESS MEDITATION PRACTICE IN MALIGNANT GLIOMA PATIENTS THROUGHOUT CONCOMITANT RADIATION AND TEMOZOLOMIDE: A FEASIBILITY STUDY. (11th November 2019) - Randazzo, Dina; Jackman, Jenny; Herndon, James; Affronti, Mary; Lipp, Eric; Cort, Nicole; Desjardins, Annick; Johnson, Margaret; Landi, Daniel; Ashley, David; Friedman, Henry; Glass, Oliver; et al.
Abstract: With a bleak prognosis for malignant glioma, maintaining quality of life (QoL) and decreasing distress of the patient are important in the clinical care of the patient. Mindfulness meditation is a mind-body therapy that has been recently investigated in the oncology field as a non-pharmacological strategy to ameliorate cancer symptoms and to improve QoL. This practice has not been studied in the primary brain tumor population. We initiated a pilot study among newly diagnosed brain tumor patients with the hypothesis that mindfulness meditation practice may benefit the patient by decreasing stress and anxiety and provide a means to cope with their new diagnosis. The specific aim of this pilot study is to determine the feasibility of a mindfulness meditation program to this population during standard of care chemoradiation and to determine whether it merits additional research in a subsequent trial. The intervention consists of six weekly one hour telephone-based mindfulness sessions followed by one in- person mindfulness session consisting of: mindfulness and healing, understanding stress, abiding in kindness, working with difficult emotions, finding peace, going forward and living fully. Subjects are provided with downloadable guided meditations. We plan to enroll fifteen newly diagnosed WHO grade III or IV malignant glioma subjects prior to their 6 week chemoradiation course. We will determine the percentage of subjects approached vs enrolled, number of sessions that each subject attends, completion of study questionnaires and satisfaction of the subjects. QoL surveys include: Functional Assessment of Cancer Therapy- Brain, Functional Assessment of Cancer Therapy- Cognitive Function, Pittsburgh Sleep Quality Index, Functional Assessment of Chronic Illness Therapy-Fatigue and the Five Facet Mindfulness Questionnaire – short form. 13 subjects have been approached and 8 signed consent over a two-month period. We will provide final study results at time of presentation.